First-Order Three-Point Boundary Value Problems at Resonance Part III - Mesliza Mohamed; Bevan Thompson; Muhammad Sufian Jusoh (Journal of Applied Mathematics)
The main purpose of this paper is to investigate the existence of solutions of BVPs for a very general case in which both the system of ordinary differential equations and the boundary conditions are nonlinear. By employing the implicit function theorem, sufficient conditions for the existence of three-point boundary value problems are established.